Editorial Note: Makara Human Behavior Studies in Asia’s Responds to Political Challenges in Scientific Publication - Jaya, Edo S.; Sekarasih, Laras; Shadiqi, Muhammad Abdan; Riantoputra, Corina D. S. (Makara Human Behavior Studies in Asia, 2022)
Three challenges of political nature were identified in 2022: increasing number of institutions in many countries in Asia to require journal article publication for graduation of an academic degree, changes in Journal Citation Index (JCITM) policy, and a retraction case in Journal of Cross-Cultural Psychology. As a response to these challenges, Makara Human Behavior Studies in Asia made several changes. First, we now publish incrementally to accommodate the requirement to publish in time. In Indonesia, as well as in many parts of Asia, publications in journals are increasingly used to satisfy administrative requirements. We have received requests for faster publication due to graduation requirements from authors from Indonesia, Malaysia, and Pakistan. The importance of journal publication is increasing in the region. Second, the everchanging scientific landscape triggers a response from Clarivate Analytics that decided to include Journal Impact Factor (JIFTM) in the subsequent publication of the Journal Citation Reports (JCRTM) in 2023.